Gender Disparities in Livestock Management and Control over Livestock Income in Erstwhile, FATA, Khyber Pakhtunkhwa-Pakistan - Naz, Shaista; Khan, Oqba; Karim, Robina (Annals of Human and Social Sciences, 2023)
Current study examined gender disparities in livestock management and control over livestock income in erstwhile FATA (Federally Administered Tribal Areas), Khyber Pakhtunkhwa, Pakistan. For this, data were collected from 323 women respondents through questionnaire. Data were analysed using frequencies, percentages, and dummy variable approaches in simple regression. Results demonstrated the existence of gender inequality in livestock ownership, with men exhibiting a higher percentage of total livestock ownership. But, it was found that women had a more challenging workload in livestock management activities than men did. The dummy variable approach showed that women allocated more time than men. Women are responsible for managing more livestock because they work more hours, which gives them more control over livestock earnings as compared to men. To make a fair division of resources for gender equality both in the livestock sector and for broader development, the study recommends distributing resources based on their merit instead of according to gender.